Employees Mindfulness Impact On Project Success In Information Technology Industry Of Pakistan: Explicating The Sequential Mediating Mechanism And Interaction Effects - Khan, Jabran (2022)
This study employed proactive motivation framework, and proposed that employees' mindfulness influence IT project success directly and indirectly through innovative work behavior and psychological hardiness. The study also proposed the moderating role of inclusive leadership on the relationship between employees' mindfulness and psychological hardiness – with high inclusive leadership; the relationship will be strengthened.